Neurosentimentalism and Moral Agency. - Gerrans, Philip; Kennett, Jeanette (Mind (0026-4423), 2010)
Metaethics has recently been confronted by evidence from cognitive neuroscience that tacit emotional processes play an essential causal role in moral judgement. Most neuroscientists, and some metaethicists, take this evidence to vindicate a version of metaethical sentimentalism. In this paper we argue that the ‘dual process’ model of cognition that frames the discussion within and without philosophy does not do justice to an important constraint on any theory of deliberation and judgement. Namely, decision-making is the exercise of a capacity for agency. Agency, in turn, requires a capacity to conceive of oneself as temporally extended: to inhabit, in both memory and imagination, an autobiographical past and future. To plan, to commit to plans, and to act in accordance with previous plans requires a diachronic self, able to transcend the present moment. While this fact about agency is central to much of moral philosophy (e.g. in discussions of autonomy and moral responsibility) it is opaque to the dual process framework and those meta-ethical accounts which situate themselves within this model of cognition. We show how this is the case and argue for an empirically adequate account of moral judgement which gives sufficient role to memory and imagination as cognitive prerequisites of agency. We reconsider the empirical evidence, provide an alternative, agentive, interpretation of key findings, and evaluate the consequences for metaethics.